The UNCRC: The Voice of Global Consensus on Children's Rights?. Issue 1 (2nd January 2018) - Quennerstedt, Ann; Robinson, Carol; I'Anson, John
ABSTRACT: That the United Nations Convention on the Rights of the Child (UNCRC) encompasses contradictions is known. Despite this knowledge, attention to conflicting aspects within the convention is limited, and instead, the assumption that the convention represents an international consensus on the meaning of children's human rights seems to be widespread in policy and academic work. Furthermore, the available literature within the field of children's rights is largely silent regarding precise and elaborated knowledge about the inherent contradictions within the UNCRC. This paper expands upon and specifies the knowledge about consensus and inconsistencies within the convention. Through an in-depth study of the drafting process of the UNCRC, the paper identifies and displays both contradictions within the convention, and ways in which the text of the convention can be seen to express consensus. The analysis shows how a certain consensus was produced for respectively civil and political rights, and socio-economic rights, but that different and inconsistent children's rights logics underlay the formation of these respective consensus-formations.